Assessment of Biology Majors’ Versus Nonmajors’ Views on Evolution, Creationism, and Intelligent Design - Paz-y-Miño C., Guillermo (Evolution (N Y), 2008)
The controversy around evolution, creationism, and intelligent design resides in a historical struggle between scientific knowledge and popular belief. Four hundred seventy-six students (biology majors n=237, nonmajors n=239) at a secular liberal arts private university in Northeastern United States responded to a five-question survey to assess their views about: (1) evolution, creationism, and intelligent design in the science class; (2) students’ attitudes toward evolution; (3) students’ position about the teaching of human evolution; (4) evolution in science exams; and (5) students’ willingness to discuss evolution openly. There were 60.6% of biology majors and 42% of nonmajors supported the exclusive teaching of evolution in the science class, while 45.3% of nonmajors and 32% of majors were willing to learn equally about evolution, creationism, and intelligent design (question 1); 70.5% of biology majors and 55.6% of nonmajors valued the factual explanations evolution provides about the origin of life and its place in the universe (question 2); 78% of the combined responders (majors plus nonmajors) preferred science courses where evolution is discussed comprehensively and humans are part of it (question 3); 69% of the combined responders (majors plus nonmajors) had no problem answering questions concerning evolution in science exams (question 4); 48.1% of biology majors and 26.8% of nonmajors accepted evolution and expressed it openly, but 18.2% of the former and 14.2% of the latter accepted evolution privately; 46% of nonmajors and 29.1% of biology majors were reluctant to comment on this topic (question 5). Combined open plus private acceptance of evolution within biology majors increased with seniority, from freshman (60.7%) to seniors (81%), presumably due to gradual exposure to upper-division biology courses with evolutionary content. College curricular/pedagogical reform should fortify evolution literacy at all education levels, particularly among nonbiologists.